Challenges in minimizing copper dissolution for lead free wave soldering in surface mount technology going towards green manufacturing - Arunasalam, Mageswaran; Leman, Zulkiflle; Baharudin, B. T. Hang Tuah; Sulaiman, Shamsuddin; Das, Charles Santhakumar Anthony (Springer Nature, 2022)
In surface mount technology, development toward green manufacturing by converting all leaded soldering processes to lead free soldering process has created a lot of challenges mainly in wave soldering process which led to copper dissolution to assemble board causing it to be scrapped if not contained. The paper aims to propose a workable and practical solution to reduce extensive copper dissolution in assemble board and expand the cycle of allowable rework in assemble board. The work was carried out using Six Sigma methodology with defining the problem and research goals, measure the details in various aspects of current process, analyse data to identify potential root cause in a process, improve the process and control the process through experimental approaches. Main factors contributing to copper dissolution were identified and analysed. Total of five factors were identified namely the printed circuit board (PCB) finishing and copper layer construction in PCB, component terminal and led finishing, soldering flux usage and solder alloy composition, environment control with the use of Nitrogen tunnelling and the last factor was on the process itself which was from the in-contact process with molten turbulence soldering or non-contact process with intrusive soldering. Combined controlled factors contributing to minimization of copper dissolution by reducing the direct contact time to molten solder with optimize solder alloy composition and process control was formulated. An increase of sixty percentage of boards with lower copper dissolution going through the lead free wave soldering and rework soldering were obtained, another forty percent reduction of board being scrapped were also obtained with boards going through the molten solder up to triple times.